The Emergence of Hong Kong as a World Centre for Chinese Protestant Bible Publishing and Distribution, 1948-51 - Mak, George Kam Wah (Studies in church history, 2025)
The Chinese Civil War (1946-9) and the Korean War (1950-3) contributed to the beginning of Hong Kong's evolution from a British colony occupying a geographically peripheral position in South China, to a world centre for Chinese Protestant Bible publishing and distribution in the Cold War era. In 1948, the China Bible House (CBH), the de facto national Bible society of China, decided to establish an emergency office in Hong Kong, responding to the prospect of the Communist takeover of China. Subsequently, as the Korean War unfolded, the CBH, owing to political pressure, desired to sever its connection with the emergency office in 1951. This resulted in the transition of the emergency office into the Hong Kong Bible House (HKBH), the British and American Bible societies' agency for Chinese Bible publishing and distribution. Thanks to the work of the HKBH, Hong Kong came to be the major source of Bibles for Chinese Protestants outside mainland China.